2005
DOI: 10.4049/jimmunol.175.2.1022
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation ofCD1D1by Ets Family Transcription Factors

Abstract: CD1 molecules are MHC class I-like glycoproteins specialized in presenting lipid/glycolipid Ags to T cells. The distinct cell-type specific expression of CD1D1 plays an important role in the development and function of NKT cells, a unique subset of immunoregulatory T cells. However, the mechanisms regulating CD1D1 expression are largely unknown. In this study, we have characterized the upstream region of the CD1D1 gene and identified a minimal promoter region within 200 bp from the translational start site of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 69 publications
1
29
0
1
Order By: Relevance
“…Despite the Ets-binding domain on the regulatory regions of CD1d [28] and BIC (pri-microRNA-155) gene [40], it is still unknown whether Ets-1 regulates their expression in B cells. We confirmed the correlations in DCs and further observed that Ets-1 directly regulates CD1d.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the Ets-binding domain on the regulatory regions of CD1d [28] and BIC (pri-microRNA-155) gene [40], it is still unknown whether Ets-1 regulates their expression in B cells. We confirmed the correlations in DCs and further observed that Ets-1 directly regulates CD1d.…”
Section: Discussionmentioning
confidence: 99%
“…Ets family transcription factors transcriptionally regulate CD1d1 and BIC (Pri-miR-155) [28,40]. We surveyed the expression of Ets-1 in SLE mice by real-time PCR, and the result showed decreased levels of Ets-1 in SLE mice compared with those of the controls (Fig.…”
Section: Ets-1 Also Regulates the Expression Of Cd1dmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of control ensures simultaneous expression of the key players required for endogenous lipid antigen presentation. Previously, several other transcription factors have been implicated in the regulation of CD1d expression in different cell types, including Ets family members (in hematopoietic cells) (55), retinoic acid receptor (in dendritic cells and mature adipocytes) (56), and PPAR␥ (in mature adipocytes) (29). However, we consider it unlikely that CD1d is under direct control of PPAR␥ during adipocyte differentiation as (i) we could not detect prominent PPAR␥ binding sites in a 200-kb chromosomal region surrounding the CD1d gene in mature adipocytes (41,42) or after short term stimulation (1 h) of mature 3T3-L1 adipocytes with the PPAR␥ ligand rosiglitazone (43) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the effects of LEF-1 on the expression of the CD1D gene are limited to the regulation of the distal promoter of the CD1D gene. Together with the known CD1D transcriptional regulators SP1, Ets families, and all-trans-retinoic acid (17,32,33), our results suggest a complicated regulatory mechanism involved in the regulation of the cell-type-specific expression of the human CD1D gene.…”
Section: Discussionmentioning
confidence: 97%